Review and trend analysis of slow tourism as an emerging trend in the Indonesian tourism industry: A study of why there is lack of extensive discussion on this topic - Supina, Supina; Ichsan Banse, Justin Mochammad (Universitas Pendidikan Indonesia, 2023)
ABSTRACTThe COVID-19 pandemic has led to a surge in the appeal of